2015
DOI: 10.1016/j.stemcr.2015.03.006
|View full text |Cite
|
Sign up to set email alerts
|

SOX2 Reprograms Resident Astrocytes into Neural Progenitors in the Adult Brain

Abstract: SummaryGlial cells can be in vivo reprogrammed into functional neurons in the adult CNS; however, the process by which this reprogramming occurs is unclear. Here, we show that a distinct cellular sequence is involved in SOX2-driven in situ conversion of adult astrocytes to neurons. This includes ASCL1+ neural progenitors and DCX+ adult neuroblasts (iANBs) as intermediates. Importantly, ASCL1 is required, but not sufficient, for the robust generation of iANBs in the adult striatum. These progenitor-derived iANB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
186
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(191 citation statements)
references
References 68 publications
4
186
1
Order By: Relevance
“…It has been shown that SOX2 is important in the maintenance of pluripotency, but it also promotes neural progenitor ground state by inhibiting further neuronal differentiation [54]. More recently, it has been shown that SOX2 expression in astrocytes effectively reprograms these cells to the neural progenitor/precursor stage [55]. Our results show that even partial reduction in FMRP levels is sufficient to induce an increase in SOX2, promoting a delay in neurodevelopment, explaining the more primitive neural phenotype observed in FX-hNPCs than in controls.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that SOX2 is important in the maintenance of pluripotency, but it also promotes neural progenitor ground state by inhibiting further neuronal differentiation [54]. More recently, it has been shown that SOX2 expression in astrocytes effectively reprograms these cells to the neural progenitor/precursor stage [55]. Our results show that even partial reduction in FMRP levels is sufficient to induce an increase in SOX2, promoting a delay in neurodevelopment, explaining the more primitive neural phenotype observed in FX-hNPCs than in controls.…”
Section: Discussionmentioning
confidence: 99%
“…In the adult CNS, retroviral delivery of Sox2 has been found to directly or indirectly reprogram resident astrocytes into induced neurons in the injured adult cerebral cortex (45)(46)(47). Importantly, there is a cellular progression for Sox2-mediated conversion of adult astrocytes to neurons, involving the neural commitment of progenitors (46).…”
Section: Rit1 Controls Neurogenesismentioning
confidence: 99%
“…In the adult CNS, retroviral delivery of Sox2 has been found to directly or indirectly reprogram resident astrocytes into induced neurons in the injured adult cerebral cortex (45)(46)(47). Importantly, there is a cellular progression for Sox2-mediated conversion of adult astrocytes to neurons, involving the neural commitment of progenitors (46). These induced adult neuroblasts are capable of in vivo proliferation and generate mature neurons when supplied with neurotrophic factors or following small-molecule treatment (46,47), which may provide a novel strategy for neuronal regenerative therapy.…”
Section: Rit1 Controls Neurogenesismentioning
confidence: 99%
See 2 more Smart Citations